Breast silicone implants’ pericapsular impairment: current underdiagnosed status - de Faria Castro Fleury, Eduardo (Frontiers in Surgery, 2023)
Many complications related to silicone implants have been reported recently, from clinical symptoms manifestations to association with some specific types of cancer. During the early 2010s, it was believed that implants were biocompatible and inert to the human body and that gel bleeding/leakage events were rare and without repercussions for the human body. However, at the end of 2010s, several studies pointed out that gel bleeding was more frequent than previously believed, and the pathogenic potential of free silicone should not be ignored. The Food and Drug Administration recommends performing magnetic resonance imaging in asymptomatic patients 5–6 years after implant placement. The descriptors in the Breast Imaging and Reporting Data System lexicon seem outdated for classifying the new generations of implants with cohesive gel, which hinders the diagnosis of device complications. In this review, supported by our research data publications related to silicone implants for 6 years on a prospective study protocol, most of them being original articles, we summarized the main complications observed in clinical practice and discuss the impact of these changes on patients’ outcomes focusing on the pericapsular space.